2005
DOI: 10.1111/j.1365-2141.2005.05440.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of epoetin‐β on survival of patients with lymphoproliferative malignancies: long‐term follow up of a large randomized study*

Abstract: SummaryRecent studies have suggested that epoetin treatment of anaemia may influence the survival of patients with cancer. We conducted an analysis of long-term survival in patients with lymphoproliferative malignancies treated with epoetin-b or placebo in a large-scale study. This was a randomized, double-blind trial in which patients with transfusion-dependent anaemia and lymphoproliferative malignancy received epoetin-b 150 IU/kg or placebo three times weekly for 16 weeks. Long-term survival data were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 20 publications
0
20
0
1
Order By: Relevance
“…Other studies were, however, designed to assess the effects of epoetin-b on survival and/or disease progression (Henke et al, 2003;Aapro et al, 2008) or Hb response to treatment (Strauss et al, 2008). Long-term follow-up information, up to 60 months, was available for overall survival in four studies (Henke et al, 2003;Ö sterborg et al, 2005;Aapro et al, 2008;Strauss et al, 2008) and for tumour progression in three studies (Henke et al, 2003;Aapro et al, 2008;Strauss et al, 2008). All reported adverse events were also reviewed against a prespecified list of TEEs, the definition of which was consistently applied across all studies.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies were, however, designed to assess the effects of epoetin-b on survival and/or disease progression (Henke et al, 2003;Aapro et al, 2008) or Hb response to treatment (Strauss et al, 2008). Long-term follow-up information, up to 60 months, was available for overall survival in four studies (Henke et al, 2003;Ö sterborg et al, 2005;Aapro et al, 2008;Strauss et al, 2008) and for tumour progression in three studies (Henke et al, 2003;Aapro et al, 2008;Strauss et al, 2008). All reported adverse events were also reviewed against a prespecified list of TEEs, the definition of which was consistently applied across all studies.…”
Section: Methodsmentioning
confidence: 99%
“…[36][37][38][39][40] Predictors of response to ESAs include the ratio of observed to expected Hb (<0.9) and the preserved BM function, reflected by the platelet counts (>150x10 9 /L). 33,38,41 A systematic review of the use of ESAs in more than 20,000 cancer patients confirmed that their use reduced the relative risk of transfusions due to increase of erythroid responses, but there was evidence that ESAs increased mortality during ESA administration and thus decreased OS. 42 Although anemia is common in MM patients, no clear consensus exists as to the use and impact of ESAs on outcome in MM and randomized studies in MM patients are still limited.…”
Section: Regimens Neutropenia (%) Vte (%) Pn (%) Infection (%) Spm (%)mentioning
confidence: 99%
“…For the meta-analysis, this information was analysed retrospectively by reviewers blinded to treatment assignment. Four of the studies, which did evaluate the effects of epoetin-b on survival and/or disease progression (Henke et al, 2003;Ö sterborg et al, 2005;Aapro et al, 2008b) or response to treatment (Strauss et al, 2008) provided long-term (up to 60 months) follow-up information for overall survival or tumour progression. For the assessment of TEEs, all reported adverse events were reviewed against a pre-specified list of TEEs, which was applied consistently across all studies.…”
Section: Methodsmentioning
confidence: 99%
“…For these analyses, patients without events were censored at 4 weeks after the last entry in the administration record. A second set of analyses using only pooled patient data from the studies with long-term follow up in which all events were included in the analysis was performed for overall survival (Henke et al, 2003;Ö sterborg et al, 2005;Strauss et al, 2008;Aapro et al, 2008b) and time to progression (Henke et al, 2003;Strauss et al, 2008;Aapro et al, 2008b). In the study by Ö sterborg et al, 2005, patients were followed for survival but not for disease progression, therefore this study was excluded from the time to progression analyses.…”
Section: Statistical Analysesmentioning
confidence: 99%